The Study of the Role of Knowledge Management, Skills, and Attitudes on Employee Performance at the Department of Food Security, West Papua Province - Wisye Sarfi Batilmurik; Nelson Mansoara (Eduvest - Journal of Universal Studies, 2024)
This research aims to analyze the role and influence of Knowledge Management, Skill and Attitude simultaneously and partially on the performance of West Papua Province Food Security Service Employees. This research was conducted at the West Papua Province Food Security Service for one month, with a sample of 75 respondents. Data collection used a questionnaire and analysis used multiple linear regression. Based on the results of hypothesis testing, especially the F test, it was found that the research model consisting of knowledge management, skills and attitude has a positive and significant influence on work performance. Furthermore, based on the results of hypothesis testing, it was found that knowledge management, skills and attitude had a significant and partially positive influence on the performance of West Papua Province Food Security Service employees. Skill is the variable that has the most dominant influence on the performance of employees of the West Papua Province Food Security Service, while knowledge management and attitude are the second and third variables that influence the performance of employees of the West Papua Province Food Security Service.